Perilaku Buruk Siswa yang Dihadapi Guru SMA dalam Manajemen Kelas - Zahra, Rani; Arisman, Arisman; Fitri, Anisa; Rejeki, Rejeki; Muslim, Muslim (STKIP ROKANIA, 2024)
The research aims to find out the most frequently occurring things and bad student behavior faced by Indonesian language teachers in elementary schools and private schools according to the perceptions of class teachers working in the 20017-2021 academic year. Data was collected using a questionnaire developed by researchers based on an open and open approach. closed. question. The questionnaire was applied to 30 teachers in both types of schools. The most common bad behavior is chatting and joking with other people. Meanwhile, the most troublesome bad behavior is not respecting teachers. As a result, teachers must learn appropriate behaviors that will most likely maximize available instructional time while minimizing time and energy wasted due to student disobedience. In addition, these teachers are interested in learning the reasons for students' bad behavior.